The Leswika geodatabase: a rocks and colouring materials library in southern Africa - (:unkn) unknown (My University, 2022)
Prehistorical raw mineral and materials studies have increased during the past decades. Mineral resources, mainly rocks and ochres, were used in the past in every-day life to produce tools, weapons, cosmetics or even during ritual. They therefore offer great opportunity to interrogate the behaviour and mobility of past communities. Understanding the choices made by individuals and communities in the past requires knowledge of the raw materials available at the time and their geological properties before and after potential anthropic modifications. We – as part of a multi-disciplinary team – are building a library of southern African natural rocks and ochres for use by researchers and scientists, with a focus on the palaeo- and geosciences. The Leswika Geodatabase consists of both a physical geological library and an online database. The material library of rocks and ochres will be housed at the University of the Witwatersrand, Johannesburg, and will be freely accessible. The online geodatabase will be open access and will combine geographical, geological and geochemical data. The first stage of the project has been initiated at a selection of archaeologically-rich areas of southern Africa. Here we present our project aims and progress, and call for collaborations to build up a robust raw materials library, which will benefit the archaeological community and encourage cross-disciplinary and intra-site collaboration.
Keywords: African Research